(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article provides examples from practice the author’s work when teaching a foreign language in the classroom, justifies the effectiveness of using various methods in the process studying a foreign language at a technical university, the article is devoted to the effective use of information and communication tools.